2012
DOI: 10.1002/jcla.21507
|View full text |Cite
|
Sign up to set email alerts
|

New Sandwich‐Type Enzyme‐Linked Immunosorbent Assay for Human MxA Protein in a Whole Blood Using Monoclonal Antibodies Against GTP‐Binding Domain for Recognition of Viral Infection

Abstract: We have developed a new ELISA for measuring MxA protein in human whole blood using mAbs specific for the GTP-binding domain of MxA. This ELISA has analytical performance enough for routine clinical assay and can be used in detecting the possibility of viral infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Moreover, a deficiency in the receptor for IFN is reported to increase the severity of respiratory viral infection ( 63 ). MxA has been found to be elevated in common respiratory viral infections as well as common viral gastrointestinal infections ( Table 2 ) ( 17 , 25 27 , 64 , 65 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a deficiency in the receptor for IFN is reported to increase the severity of respiratory viral infection ( 63 ). MxA has been found to be elevated in common respiratory viral infections as well as common viral gastrointestinal infections ( Table 2 ) ( 17 , 25 27 , 64 , 65 ).…”
Section: Discussionmentioning
confidence: 99%
“…5,6,9,19 The thresholds chosen differed from 1 study to another, ranging from 36.7 ng/mL to 500 ng/mL, 6,19,20 related to methodologic MxA detection differences, ROC curve analyses, or desired Se or Sp. In our study, MxA levels above the 200-ng/mL threshold predicted a viral infection with useful LRs for practice.…”
Section: Validation Of Mxa As a Marker Of Viral Infectionmentioning
confidence: 99%
“…27 The use of this marker of viral infection is therefore also promising in specific patient populations at high risk of infectious complications. The recent development of a sandwichtype enzyme-linked immunosorbent assay for human MxA protein in blood in a 96-well plate format 19 could facilitate the automation of MxA measurement and its introduction in the routine diagnostic laboratory.…”
Section: Validation Of Mxa As a Marker Of Viral Infectionmentioning
confidence: 99%
“…Many studies have shown that MxA protein expression in peripheral blood is a sensitive and specific marker of viral infection [24][25][26][27][28][29][30][31]. Higher MxA levels are found in viral infections compared with bacterial infections because MxA protein is induced exclusively by type I IFN and not by IFN-gamma, IL-1, TNF-alpha or any of the other cytokines expressed during bacterial infection [32].…”
Section: Host Immune Response Assaymentioning
confidence: 99%